Attributes of irrigated rice and soil solution as affected by salinity levels of the water layer - Fraga, Thiago Isquierdo(Federal University of Rio Grande do Sul); Carmona, Felipe de Campos(UFRGS Graduate Program of Soil Science); Anghinoni, Ibanor(UFRGS Graduate Program of Soil Science); Marcolin, Elio(IRGA) (Revista brasileira de ciência do solo, 2010)
In the State of Rio Grande do Sul, Brazil, flooded rice fields using Patos Lagoon as the source of water for irrigation are subject to be damaged by salinity, since this source is bound to the sea on its southern end. The sensitivity of rice is variable during plant development, being higher in the seedling and reproductive periods. However, there is not enough information about the behavior of plants under salt stress during the course of its development, especially in the vegetative stage. This study evaluated the effect of different levels of salinity of irrigation water on the salinity of soil solution over time and on some plant attributes, during the vegetative stage of rice. The study was conducted in a greenhouse, where seeds of the variety IRGA 424 were sown in pots and irrigated with water with electrical conductivity (ECi) levels of: 0.3, 0.75, 1.5, 3.0 and 4.5 dS m-1; from the tillering initiation (V4) until the panicle initiation (PI). The evaluations made were the electrical conductiviy of soil solution (ECe), the dry biomass of plants and stems, tillering, height and the transpiration of plants. The ECe increased with the ECi over time, and was determined by water transpiration flux in pots. The ECe values at the end of the experiment were high and, in most cases, higher than the critical values for flooded rice. The growth attributes of rice were negatively affected from ECi of 2.0 dS m-1 and ECe of 4.0 dS m-1. No Rio Grande do Sul, lavouras de arroz irrigado que utilizam como fonte hídrica a Laguna dos Patos estão sujeitas a sofrer danos pela salinidade, uma vez que esse manancial liga-se ao mar em sua extremidade sul. A sensibilidade do arroz é variável no decorrer do ciclo de desenvolvimento da cultura, sendo maior no período de plântula e no reprodutivo. No entanto, pouco se sabe sobre o comportamento das plantas em condições de estresse salino no decorrer do seu ciclo de desenvolvimento, principalmente no período vegetativo. Este trabalho teve como objetivo avaliar o efeito de diferentes níveis de salinidade da água de irrigação sobre a salinidade da solução do solo e sobre atributos de planta durante o período vegetativo do arroz. O trabalho foi conduzido em casa de vegetação, onde o cultivar IRGA 424 foi semeado em vasos, que foram irrigados com água com níveis de condutividade elétrica (CEi) de: 0,3; 0,75; 1,5; 3,0; e 4,5 dS m-1 a partir do início do perfilhamento (V4) até a diferenciação do primórdio floral (DPF). Foram avaliados a condutividade elétrica da solução do solo (CEe), a matéria seca da parte aérea e dos colmos, o perfilhamento, a estatura e a transpiração das plantas. A CEe aumentou com a CEi ao longo do tempo e foi determinada pelo fluxo de transpiração de água em ambiente confinado. Os valores de CEe atingidos no final do trabalho foram elevados e, na maioria dos casos, superiores aos valores considerados críticos para o arroz irrigado. Os atributos de crescimento do arroz irrigado foram alterados negativamente a partir da CEi de 2,0 dS m-1 e da CEe de 4,0 dS m-1.